المصادر اللغوية في تخمين معاني المفردات في قراءة النص العربي لغير الناطقين بالعربية = Al-masadir al-lughawiyyah fi takhmin ma'ani al-mufradat fi qiraat al-nass al-arabiyy lighairi al-natiqin bi al-arabiyyah - Mustapha, Nik Hanan; Zulkifli, Hidayatul Hasanah; Mustapha, Nik Farhan (Kolej Islam Darul Ridzuan, Perak, 2012)

(untitled)
Guessing word meaning from context plays an important role in increasing the level of reading comprehension of second or foreign language learners. Despite various taxonomies for guessing word meanings, most of them generally fall into two categories: linguistic sources and non-linguistic sources. This study investigates the use of second language sources within the linguistic category in guessing the meaning of words. A sample of 10 university students participated in this introspective study by performing reading tasks on selected Arabic texts. Data was then gathered through think aloud procedures and interviews. Results indicated that students utilize linguistic sources at different levels: word, sentence and discourse, with morphological knowledge is used far more often than the remaining sources. This lends support to the need for promoting the role of guessing word meaning in Arabic reading comprehension.